Answer:
(
2
x
−
6
)
2
+
4
(
2
x
−
6
)
+
3
=
0
Simplify the left side.
Tap for more steps...
(
2
x
−
6
)
2
+
8
x
−
21
=
0
Use the quadratic formula to find the solutions.
−
b
±
√
b
2
−
4
(
a
c
)
2
a
Substitute the values
a
=
4
,
b
=
−
16
, and
c
=
15
into the quadratic formula and solve for
x
.
16
±
√
(
−
16
)
2
−
4
⋅
(
4
⋅
15
)
2
⋅
4
Simplify.
Tap for more steps...
x
=
4
±
1
2
The final answer is the combination of both solutions.
x
=
5
2
,
3
2
Step-by-step explanation:
Answer:
Step-by-step explanation:
30).
degree ( 4 + 1 = <em>5</em> ; 1 + 1 = 2 and 2 + 2 = 4 )
31) D) Choice D
Answer:
6.5
Step-by-step explanation:
3X5=15
97.5/ 15 = 6.5